Photodynamic therapy in the combined treatment of choroidal melanoma - E.V. Samkovich; I.E. Panova; E.V. Boyko; E.M. Svistunova; A.A. Bykhovskii (Офтальмохирургия)
Purpose. To evaluate the effectiveness of the combined treatment of choroidal melanoma (CM) based on the use of PDT and Ru-106+Rh-106 brachytherapy (BT). Material and methods. Retrospective analysis was carried out in 48 patients (48 eyes) with CM. Distribution of patients according to TNM system: T1N0M0 – 2 patients, T2N0M0 – 14, T3N0M0 – 32. All patients were divided into 2 study groups: 1st group – 25 patients (25 eyes) who underwent Ru/Ro-106 BT in isolation, SOD 125.4±12.3 Gy; 2nd group – 23 patients (23 eyes) who underwent combined treatment: Ru-106+Rh-106 BT (SOD 127.3±13.6 Gy) + PDT. Diagnostics was carried out on the basis of clinical and instrumental examination including complex ultrasound with estimation of the tumor vascularization degree. Results. Application of complex organ preservation treatment, including photodynamic therapy, followed by BT promotes acceleration of rates of tumor regression in 3, 6, 12 months (p<0.05). It was reliably found that the signs of intratumoral vascularization of CM (p<0.05) decrease after a combined treatment. Acomparative analysis of the effectiveness of the two variants of organ preservation treatment of CM has shown a higher efficacy of PDT and BT, based on complete regression of the tumor and local control in a significantly larger number of patients (p<0.05). Conclusion. The results of application of PDT in the combined treatment of CM show the prospects of the method application to achieve a faster rate of tumor regression and a preventive measure of haematogenous metastasis due to necrosis and blocking of vessels feeding the tumor.